Dampak Pandemi Covid-19 Pada Aktivitas Ekspor-Impor Provinsi Lampung (Studi Pada PT. Pelabuhan Indonesia Cabang Panjang) - Suryani Suryani; Melan Susanty P (Universitas Malahayati, 2022)
This study aims to determine the development of export and import activities in Lampung Province during the Covid-19 pandemic, especially at the Port of Panjang-Bandar Lampung. The type of research used is qualitative research, and the sampling technique uses purposive sampling method. This research is expected to provide information or knowledge for exporters, importers, related institutions, especially port managers. Based on the results of the study, export and import activities in Lampung Province through the Port of Panjang-Bandar Lampung experienced a significant decline during the Covid-19 pandemic. The impact of the Covid-19 pandemic is not only on the health sector, but also has a significant impact on the economic and business sectors, especially in export and import activities.